2017
DOI: 10.1371/journal.pone.0179764
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir based treatment of chronic hepatitis C genotype 3 infections—A Scandinavian real-life study

Abstract: Background and aimsChronic hepatitis C virus (HCV) genotype 3 infection with advanced liver disease has emerged as the most challenging to treat. We retrospectively assessed the treatment outcome of sofosbuvir (SOF) based regimes for treatment of HCV genotype 3 infections in a real life setting in Scandinavia.MethodsConsecutive patients with chronic HCV genotype 3 infection were enrolled at 16 treatment centers in Denmark, Sweden, Norway and Finland. Patients who had received a SOF containing regimen were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
(33 reference statements)
5
21
0
1
Order By: Relevance
“…Therefore our data underscores the importance of prolonging treatment duration to 24 weeks, as well as adding RBV when feasible, to obtain an improvement in SVR. These findings are supported by and consistent with other three reports in abstract form from other Italian regions [10][11][12] and two European studies [13,14]. The beneficial role of RBV in treating G3 cirrhotic patients is in fact suggested by improved virological rates in RBV-containing regimens also in the UK EAP study though the total number of patients treated without RBV was small and robust conclusion cannot be drawn [13].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore our data underscores the importance of prolonging treatment duration to 24 weeks, as well as adding RBV when feasible, to obtain an improvement in SVR. These findings are supported by and consistent with other three reports in abstract form from other Italian regions [10][11][12] and two European studies [13,14]. The beneficial role of RBV in treating G3 cirrhotic patients is in fact suggested by improved virological rates in RBV-containing regimens also in the UK EAP study though the total number of patients treated without RBV was small and robust conclusion cannot be drawn [13].…”
Section: Discussionsupporting
confidence: 86%
“…The beneficial role of RBV in treating G3 cirrhotic patients is in fact suggested by improved virological rates in RBV-containing regimens also in the UK EAP study though the total number of patients treated without RBV was small and robust conclusion cannot be drawn [13]. Similar results are reported in the Scandinavian study where the addition of RBV even for 12 weeks' treatment showed a trend toward higher SVR12 [14]. However, our results are in contrast with a sub-analysis of an heterogeneous French early access program study by Hezode et al, which showed a lower SVR rates in 205 G3 cirrhotic patients treated for 24 weeks with the same regimens: SOF + DCV had 86% SVR12, while SOF + DCV + RBV had 82% SVR12 [15].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The EVR and ETR rates are almost equal in patients with different liver textures. Dalgard et al. (2017) administered Sofosbuvir plus Ribavirin therapy to hepatitis C virus genotype 3 patients in Scandinavian countries and reported SVR12 of 90% in compensated cirrhotic patients compared with 100% in non-cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early virological response was achieved with DAAs in short duration that was not achieved by interferon therapy after long time. In Scandinavian countries, [3] injected DAAs to HCV genotype 3 patients and noted Sustained virological response in cirrhotic and non-cirrhotic patients that was 90% and 100. We have 932 patients under treatment for HCV genotype 3, the 29 cases with same Hepatitis C Virus genotype and 3 with other HCV genotypes in interferon base therapy.…”
Section: Discussionmentioning
confidence: 99%